Effects of different Incentives on Attrition and Fieldwork Effort in Telephone Household Panel Surveys - Oliver Lipps (Survey Research Methods, 2010)
Little is known about sample behavior and fieldwork effects of different incentives introduced in a household panel survey. This is especially true for telephone surveys. In a randomized experiment, the Swiss Household Panel implemented one prepaid and two promised non-monetary incentives in the range of 10 to 15 Swiss Francs (7-10 EUR), plus a no incentive control group. The aim of the paper is to compare effects of these incentives especially on cooperation, but also on sample selection and fieldwork effort, separated by the household and the subsequent individual level. We find small positive cooperation effects of the prepaid incentive on both the household and the individual level especially in larger households. Sample composition is affected to a very minor extent. Finally, incentives tend to save fieldwork time and partially the number of contacts needed on the individual level.